Analysis of the CAMEL Ratio in Predicting Bankruptcy Using the Altman Z-Score Approach: Evidence from Islamic Commercial Banks in Indonesia (2010–2021) - Erliza Ambun Lubis; Darwis Harahap; Abdul Nasser Hasibuan (PT. Altaf Publishing Corp, 2025)
This study aims to analyze the CAMEL ratio (Capital, Asset, Management, Earning, and Liquidity) in predicting bankruptcy in Sharia Commercial Banks using the Altman Z-Score approach. The CAMEL components analyzed include the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Return on Assets (ROA), Financing to Deposit Ratio (FDR), and Operating Costs to Operating Income (BOPO). The study uses quantitative descriptive methods with panel data regression and the Granger causality test, based on quarterly financial reports from 2010 to 2021 obtained from OJK and Bank Indonesia publications. The findings reveal that under the Fixed Effect Model (FEM), ROA and CAR significantly influence the Altman Z-Score, while FDR, NPF, and BOPO show no significant impact. The Granger causality results indicate that CAR, FDR, BOPO, and ROA maintain healthy performance ratios, implying that the overall Sharia banking system remains financially sound, although certain components reflect potential early warnings of financial distress. These results highlight the importance of consistent monitoring through the CAMEL framework and Altman Z-Score to anticipate systemic banking risks.